2013
DOI: 10.1073/pnas.1216464110
|View full text |Cite
|
Sign up to set email alerts
|

Community dynamics and ecosystem simplification in a high-CO 2 ocean

Abstract: Disturbances are natural features of ecosystems that promote variability in the community and ultimately maintain diversity. Although it is recognized that global change will affect environmental disturbance regimes, our understanding of the community dynamics governing ecosystem recovery and the maintenance of functional diversity in future scenarios is very limited. Here, we use one of the few ecosystems naturally exposed to future scenarios of environmental change to examine disturbance and recovery dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 50 publications
7
82
1
Order By: Relevance
“…Previous studies along pH gradients near Mediterranean volcanic seeps have demonstrated that although seawater acidification with CO 2 can benefit some organisms, such as heterokont algae, it is detrimental to most sessile calcified species and leads to a reduction in biodiversity (Porzio et al, 2011;Johnson et al, 2013;Kroeker et al, 2013b). Here we show that CO 2 seeps may also be useful for studying the effects of ocean acidification on plankton.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies along pH gradients near Mediterranean volcanic seeps have demonstrated that although seawater acidification with CO 2 can benefit some organisms, such as heterokont algae, it is detrimental to most sessile calcified species and leads to a reduction in biodiversity (Porzio et al, 2011;Johnson et al, 2013;Kroeker et al, 2013b). Here we show that CO 2 seeps may also be useful for studying the effects of ocean acidification on plankton.…”
Section: Discussionmentioning
confidence: 66%
“…Natural CO 2 seeps are being used to examine the response of coastal ecosystems to ocean acidification (HallSpencer et al, 2008). Hundreds of benthic species have been investigated in these settings (Fabricius et al, 2011;Porzio et al 2011;Inoue et al, 2013;Kroeker et al, 2013b). Meroplanktonic calcified organisms such as juvenile gastropods and foraminifera are adversely affected as CO 2 levels increase (Cigliano et al, 2010), but carbon dioxide seeps have not so far been used for the study of ocean acidification on holoplankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the projected near-future conditions presented in these analyses (figure 2), sea urchin densities are similar to control sites at tropical vents (K.E.F. 2013, unpublished data) and temperate vents [72,73]. In addition, the abundance of small mobile grazers (primarily gastropods) does not differ among the low pH and control sites at the temperate vents [74].…”
Section: (D) Herbivoresmentioning
confidence: 87%
“…The great challenge of predicting the effects of acidification on SAV communities stems from the fact that indirect effects can be at least as important as the direct effects on individual plants, but are much more difficult to predict (Kroeker et al 2013a(Kroeker et al , 2013b. In the Chesapeake, we must consider the impacts of coastal acidification on the competitive balance between submerged vegetation and competing macroalgae and epiphytes.…”
Section: Coastal Zone Acidificationmentioning
confidence: 99%